Analisis Pengaruh Tingkat Suku Bunga Dan Jumlah Uang Beredar Terhadap Indeks Harga Saham Gabungan (IHSG) Di Bursa Efek Indonesia (Tahun 2003 - 2008) - tri irawati (STMIK Sinar Nusantara, 2010)
Composite Stock Price Index (IHSG) were used as a barometer of economic health of a nation and as a basis for statistical analysis of recent market conditions (Current market). Another factor is the determination of the JCI is the amount of money circulating in the community will also be encouraged to see the reaction of the investment made.According to Keynes, in Wardane (2003), the interest rate is determined by supply and demand for money (determined in the money market). Changes in interest rates is not directly related to the level of JCI means H1 is rejected. Then for the next hypothesis that the money supply will affect the value of JCI (H2) is accepted. Decline in value of stock index was also influenced by a decrease in the money supply.On the whole it can be stated that the change Period JCI entirely influenced by the money supply and not directly influenced by interest rates. Independent variables affect the independent variable of 68.90% and the rest influenced by other variables that are not involved in this research.Key words : IHSG, JCI